(untitled) (Agricultural Engineering, 2017)
The object of the research consisted of a roller threshing unit with a profile elastic working surface of a parabolic type and a triangle one with rollers which turn concurrently with various angular speeds. Two rollers with 150 and 300 mm were investigated. The process of seeds separation from the threshing mass took place at its moisture of 10 to 35%. The relation of mixtures in the straw mass in a mass relation was changing within 10 to 35% with the length of stalks from 20 to 400 mm. The amount of the material provided for threshing was varied from 0.27 to 0.52 kg∙s-1∙m-1 and the slot between the rollers from 1.0 to 6.0 mm. The width of the base of notches located on the working surface of drums was within 25 to 150 mm, the height of notches on rollers was within 10 to 60 mm. Kinematic conditions of rollers operation were within 1.0 to 1.5. As a result of the research it was determined that a parabola is the optimal form of the profiled surface of rollers in a cross section. It ensures more effective seeds separation than a triangle configuration of drums. This conclusion is also confirmed by a theoretical discussion and is explained with the fact that the parabolic form of notches has a bigger surface than the triangle one and that they affect more seed-bags which leads to the increase of the seeds separation degree. The laboratory research allowed determination of rational ranges of parameters changes during flax mass threshing.